Innovative Opportunities for the Development of Communicative Culture in the Process of Teaching English Language to Future Professionals (Eurasian Journal of Learning and Academic Teaching, 2022)
This article describes the main criteria for teaching English to specialists in professional activities, provides an overview of interdisciplinary connections in the learning process and new methods of teaching English in order to form a communicative culture in English, focused on the professional activities of future graduates.